High-Intensity Interval Exercise with Blood Flow Restriction Improves Vascular Function in Obese Male Adolescents - Thitiwat Noikhammueang; Witid Mitranun (OVS LLC, 2023)
Study purpose. Obesity, a chronic metabolic disease is on the rise among children and adolescents and is a leading cause of mortality in adults worldwide. It is imperative to prevent obesity in children to lower the risk of adult obesity and cardiovascular diseases. Considering the effectiveness of exercise program, high-intensity interval exercise with blood flow restriction (HIIE-BFR) may have potential beneficial effects on the vascular functions of obese individuals. This study aimed to compare the acute effects of supramaximal high-intensity interval exercise (HIIE-SUPRA) and HIIE-BFR on the vascular function in obese adolescents. Materials and methods. The subjects were adolescent males aged 13 to 15. The crossover study was divided into two trials. The first trial was a pilot study involving five obese adolescent males whose heart rates were evaluated under four conditions of exercise: 1) HIIE-SUPRA at 170% (VO₂peak), 2) HIIE-BFR at 85% VO₂peak with 40% arterial occlusion pressure (AOP), 3) 60% AOP, and 4) 80% AOP. The second trial was conducted on ten obese adolescent males who performed HIIE-SUPRA and HIIE-BFR exercises separately, each for at least three days. Data collection was done to analyze the vascular function parameters before and after exercising (immediately, 10 min, 30 min, and 60 min after). Results. The results of the first trial showed that the mean heart rate of HIIE-BFR at 40% AOP was similar to that of HIIE-SUPRA (p>0.05). In the second trial, both types of exercises showed similar outcomes, with increased flow-mediated dilatation (FMD), while brachial-ankle pulse wave velocity (baPWV) decreased after exercise as compared to the baseline values (before exercise) (p<0.05). However, HIIE-BFR at 40% AOP demonstrated a lower rate of perceived exertion (RPE) as compared to HIIE-SUPRA (p<0.05). Conclusions. HIIE-BFR at 40% AOP was effective in regulating the RPE and acutely increasing the vascular function after exercise in obese adolescents, similar to HIIE-SUPRA.